تاثرات و اشارات نبوی کی معنویت( دعوتی، تعلیمی، ثقافتی ، قانونی پہلو ) - Dr. Muzammil kamran (Seerat Studies, 2024)
Nonverbal communication has a vital role in humans daily social communication. It consists of facial impressions, gestures and body language. Now a days it has become a current era of research. That is why , Nonverbal communication , ethics and methodology practiced by the Holy Prophet(PBUH), observed by the worthy companions and narrated & explained by the second and third ranked narrators i.e. Tab’aeen and taba tab’aeen , is a current horizon of seerah studies. Classified examples of holy seerah by ahadees are hereby presented to understand this study and to enhance the scholars to focus on this era of holy seerah , keeping in mind the purpose of study which is mentioned as under : To explore cultural heritage of Islam in respect of nonverbal communication. Nonverbal communication by the Holy Prophet (PBUH) in aspect of education pedagogy. Importance of nonverbal communication in preaching Islam as a code of conduct for life. Legislative position of facial impressions , gestures and body language of the Holy Prophet (PBUH).